" The Effect Of The Osborn Barnes Model On The Holistic Thinking Of Fourth-Grade Science Students In Biology " (Journal of the College of Basic Education, 2025)
The research aims to identify "the effect of the (Osbom Barmes) model on the comprehensive thinking of fourth-grade science students in biology." To achieve the research objective, the researchers formulated the following minor hypothesis: "There is no statistically significant difference at the (0.05) level between the average scores of the experimental group students who studied biology according to the (Osbom Bames) model and the average scores of the control group students who studied the same subject according to the usual method in the comprehensive thinking scale ." The experimental design with partial control was chosen for the two research groups. The researchers chose the secondary and preparatory day schools in Diyala Governorate Education / Baqubah District. A sample was chosen randomly consisting of (63) students distributed to the two research groups, with (31) students for the experimental group and (32) students for the control group. To achieve the research objective, the researchers prepared a scale for comprehensive thinking, which consisted of (40) items distributed over five areas. The apparent validity was extracted by presenting it to a group of arbitrators, and its stability was calculated using the Cronbach's alpha equation, which reached (0.881). After analyzing the results using the (t-test) for two independent samples, the results indicated the superiority of the experimental group that studied according to the (Osbom Bames) model over the control group that studied in the usual way in the scale of comprehensive thinking. Based on these results, the conclusions, recommendations and proposals mentioned in Chapter Four